1997
DOI: 10.1172/jci119388
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia is associated with failure of human cytotrophoblasts to mimic a vascular adhesion phenotype. One cause of defective endovascular invasion in this syndrome?

Abstract: In human pregnancy, placental cytotrophoblasts that invade the uterus downregulate the expression of adhesion receptors that are characteristic of their epithelial origin, and upregulate the expression of adhesion receptors that are expressed by vascular cells. We suggest that this transformation could be critical to endovascular invasion, the process whereby cytotrophoblasts invade the uterine spiral arterioles and line their walls (Zhou et al. J. Clin. Invest. 1997. 99: 2139-2151.). To better understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
492
5
26

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 859 publications
(537 citation statements)
references
References 33 publications
14
492
5
26
Order By: Relevance
“…Notably, immunofluorescence revealed that the particular adhesion molecule specifically localizes to proliferative CCTs in the intermediate region of the cell column (Fig. 5B) (12). Hence, N1ICD-induced VE-cadherin expression might suggest that cell column progenitors have further developed into TA-like cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Notably, immunofluorescence revealed that the particular adhesion molecule specifically localizes to proliferative CCTs in the intermediate region of the cell column (Fig. 5B) (12). Hence, N1ICD-induced VE-cadherin expression might suggest that cell column progenitors have further developed into TA-like cells.…”
Section: Discussionmentioning
confidence: 94%
“…Besides unfavorable immunological interactions of EVTs with uterine natural killer (uNK) cells (11), abnormal placental development and trophoblast differentiation are thought to contribute to the pathogenesis of gestational disorders. Indeed, CTBs isolated from preeclamptic placentae failed to appropriately differentiate into the invasive lineage in vitro and expressed an antimigratory gene signature (12,13).…”
mentioning
confidence: 99%
“…In preeclampsia, there is shallow placental cytotrophoblast invasion of uterine spiral arterioles, leading to reduced placental perfusion and consequently placental insufficiency. Both in vitro and in vivo studies show that trophoblasts obtained from patients with preeclampsia fail to undergo these alterations of adhesion molecules and pseudovasculogenesis (15,16). The molecular pathways that regulate pseudovasculogenesis may involve a vast array of transcription factors, growth factors, and cytokines (17).…”
Section: Abnormal Placentation and Placental Ischemiamentioning
confidence: 99%
“…1 It is characterized by abnormal vascular response to placentation that is associated with increased systemic vascular resistance, enhanced platelet aggregation, activation of the coagulation system and endothelial cell dysfunction. 2 An initiating event in preeclampsia has been postulated to be reduced placental perfusion that leads to widespread dysfunction of the maternal vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%